2017
DOI: 10.1093/geront/gnw258
|View full text |Cite
|
Sign up to set email alerts
|

Elder Fraud and Financial Exploitation: Application of Routine Activity Theory

Abstract: Findings support an adapted routine activity theory as a contextual model for financial victimization. Fraud most often occurred when a vulnerable elder was solicited by a financial predator in the absence of capable guardians. Prevention efforts should focus on reducing social isolation to enhance protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 32 publications
(37 reference statements)
1
96
1
Order By: Relevance
“…Elder financial exploitation (FE), also called financial elder abuse, refers to “the illegal or improper use of an elder’s funds, property, or assets,” particularly in ways that are not in the older adult’s best interest ( Hall, Karch, & Crosby, 2016 ). FE takes many forms, but perpetrators are seen in a position of trust and thus include family members, relatives, and caregivers who take older adults’ money without their consent ( DeLiema, 2017 ). Theories of FE provide guidelines for investigating key risk and protective factors ( Kemp & Mosqueda, 2005 ; Pinsker, McFarland, & Pachana, 2010 ; Rabiner, O’Keeffe, & Brown, 2004a ; Wilber & Reynold, 1996 ), with related literature highlighting the important roles of interpersonal interactions ( Baltes & Baltes, 1990 ; Carstensen, Fung, & Charles, 2003 ).…”
mentioning
confidence: 99%
“…Elder financial exploitation (FE), also called financial elder abuse, refers to “the illegal or improper use of an elder’s funds, property, or assets,” particularly in ways that are not in the older adult’s best interest ( Hall, Karch, & Crosby, 2016 ). FE takes many forms, but perpetrators are seen in a position of trust and thus include family members, relatives, and caregivers who take older adults’ money without their consent ( DeLiema, 2017 ). Theories of FE provide guidelines for investigating key risk and protective factors ( Kemp & Mosqueda, 2005 ; Pinsker, McFarland, & Pachana, 2010 ; Rabiner, O’Keeffe, & Brown, 2004a ; Wilber & Reynold, 1996 ), with related literature highlighting the important roles of interpersonal interactions ( Baltes & Baltes, 1990 ; Carstensen, Fung, & Charles, 2003 ).…”
mentioning
confidence: 99%
“…The notion that people's life circumstances and behaviors can impact scam susceptibility is consistent with routine activity theory (Cohen and Felson, 1979). Applied to the context of financial fraud (DeLiema, 2017;Holtfreter, Reisig, and Pratt, 2008), routine activity theory proposes that day-to-day behaviors/routines affect the likelihood that motivated offenders will intersect in space and time with suitable targets in the absence of capable guardianship (or measures of protection). For example, consumers who engage in risky behaviors such as responding to telemarketers, opening spam mail, and making frequent online purchases, are more likely to be exposed to scams (AARP, 1996;Reisig and Holtfreter, 2013;Van Wyk and Benson, 1997).…”
Section: Discussionmentioning
confidence: 79%
“…Alternatively, our findings suggest that having a trustworthy confidant mitigates perceived vulnerability and protects financial well-being overall. DeLiema (2018) investigated routine activity theory as a context for fraud susceptibility and found that isolation and a lack of trustworthy friends or family best distinguished those who had been defrauded from those who had not. Routine activity theory requires the convergence of three factors: an offender, a target, and the absence of others to protect the target.…”
Section: Discussionmentioning
confidence: 99%